Adopt 10 key strategies to develop fully online programs at scale. Issue 11 (February 2017) - Hope, Joan
Abstract : Fully online programs can be a good way to grow enrollment and meet student needs. But officials need to understand from the beginning what it will cost to develop, deliver, and grow a program, said Cindy Wheatley of Keypath Education. At many institutions, officials focus on developing the courses and admitting students. But they don't look ahead financially, and the programs never break even.